The relation between Parkinson’s disease and non-steroidal anti-inflammatories; a systematic review and meta-analysis - Badawoud, Amal Mohammad; Ali, Lashin Saad; Abdallah, Mahmoud S.; El Sabaa, Ramy M.; Bahaa, Mostafa M.; Elmasry, Thanaa A.; Wahsh, Eman; Yasser, Mohamed; Eltantawy, Nashwa; Eldesoqui, Mamdouh; Hamouda, Manal A. (Frontiers in Pharmacology, 2024)
Parkinson's disease (PD) is a neurological condition that typically shows up with aging. It is characterized by generalized slowness of movement, resting tremor or stiffness, and bradykinesia. PD patients' brains mostly exhibit an increase in inflammatory mediators and microglial response.Nevertheless, a variety of non-steroidal anti-inflammatory medications (NSAIDS) offered neuroprotection in animal models and preclinical trials. The current systematic review and metaanalysis were designed to try to resolve the debate over the association of NSAID use with the development of PD because the results of several studies were somehow contradictory. An intense search was performed on Scopus, PubMed, and Web of Science databases for articles relating the incidence of PD to the use of NSAIDs. Statistical analysis of the included studies was carried out using Review Manager version 5.4.1 by random effect model. The outcome was identified as the development of PD in patients who were on NSAIDs, ibuprofen only, aspirin only, and non-aspirin NSAIDs. This was analyzed using pooled analysis of odds ratio (OR) at a significance level of ≤ 0.05 and a confidence level of 95%. A statistically significant decreased risk of PD was observed in patients taking NSAIDs, Ibuprofen, and non-aspirin NSAIDs. The ORs of PD occurrence in patients who took NSAIDs, Ibuprofen, and non-aspirin NSAIDs were 0.88 (95% CI [0.8 -0.97], p=0.01), 0.73 (95% CI [0.53 -1], p=0.05) and 0.85 (95% CI [0.75-0.97], p=0.01). Meanwhile, the risk of PD in patients who took aspirin was not statistically significant. In conclusion, Ibuprofen, non-aspirin NSAIDs, and other types of NSAIDs could be associated with a reduction in PD risk.However, there was no association between aspirin intake and the development of PD.